The Field of Cultural Production among Religious Community in Higher Education Institution - Ekky Megawangi Pertiwi; Okta Hadi Nurcahyono (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2022)
The utilization practices of houses of worship in Benteng Pancasila Area of Universitas Sebelas Maret (UNS) Surakarta can be seen as a field of cultural production by religious communities in an educational environment. This study aims to discover: how houses of worship on UNS Benteng Pancasila are utilized; how agents use capital to shape cultural production; and what social impacts are created. By applying a qualitative method with a case study as an approach, this study found that: the successfully constructed habitus leads to socio-cultural religious practices with academic nature; agents instill values through narratives using cultural, social, and symbolic capital and; the social impacts include inter-religious group integration, but the interaction within it is still limited. In this case, it was revealed that the social relations formed from cultural production are still limited on the symbolic level.